Does muscle guarding play a role in range of motion loss in patients with frozen shoulder?. (October 2018) - Hollmann, L.; Halaki, M.; Kamper, S.J.; Haber, M.; Ginn, K.A.
Abstract: Study Design: Observational: cross-sectional study. Background: Idiopathic frozen shoulder is a common cause of severe and prolonged disability characterised by spontaneous onset of pain with progressive shoulder movement restriction. Although spontaneous recovery can be expected the average length of symptoms is 30 months. Chronic inflammation and various patterns of fibrosis and contracture of capsuloligamentous structures around the glenohumeral joint are considered to be responsible for the signs and symptoms associated with frozen shoulder, however, the pathoanatomy of this debilitating condition is not fully understood. Objectives: To investigate the feasibility of a muscle guarding component to movement restriction in patients with idiopathic frozen shoulder. Methods: Passive shoulder abduction and external rotation range of motion (ROM) were measured in patients scheduled for capsular release surgery for frozen shoulder before and after the administration of general anaesthesia. Results: Five patients with painful, global restriction of passive shoulder movement volunteered for this study. Passive abduction ROM increased following anaesthesia in all participants, with increases ranging from approximately 55°–110° of pre-anaesthetic ROM. Three of these participants also demonstrated substantial increases in passive external rotation ROM following anaesthesia ranging from approximately 15°–40° of pre-anaesthetic ROM. Conclusion: This case series of five patients with frozen shoulder demonstrates that active muscle guarding, and not capsular contracture, may be a major contributing factor to movement restriction in some patients who exhibit the classical clinical features of idiopathic frozen shoulder. These findings highlight the need to reconsider our understanding of the pathoanatomy of frozen shoulder. Level of evidence: Level 4. Highlights: In frozen shoulder patients large increases in range occurred following anaesthesia. Capsular contracture may not be contributing to restricted range in frozen shoulder. Muscle guarding contributes to restricted movement in some frozen shoulder patients.